Agricultural waste: Review of the evolution, approaches and perspectives on alternative uses - Duque-Acevedo, Mónica; Belmonte-Ureña, Luis J.; Cortés-García, Francisco Joaquín; Camacho-Ferre, Francisco (Global ecology and conservation, 2020)
This research provides an analysis of existing scientific production on agricultural waste from 1931 to 2018. The database was obtained from Scopus and includes a total of 3148 articles, which were analysed using the bibliometric method. This method focuses on the identification, evolution, approaches and trends referred to in the use and transformation of agricultural waste. The results of the analysis of the most specific variables, some of which are represented graphically through clusters in networking maps using VOSviewer software, establishes that agricultural waste has been studied worldwide for more than 60 years and that research on this issue has become more relevant from 1998. However, it has been in the last 13 years that more than 60% of the scientific production on this field of study has been generated. The United States, India and China are the countries with the greatest number of studies, whose central axis has been the use and exploitation of agricultural residues, derived from cereal crops, mainly wheat and corn, as they are the main producers of this type of crops. Many authors, mainly from government and academic institutions, have contributed considerably to this research topic. The evolution of their studies evidences a change in the original approach, due to the influence of the new global energy and environmental policies developed during the last decade. Undoubtedly, the international regulatory framework on sustainable development has been transforming the role of agriculture and especially the policies and strategies on the circular economy and bioeconomy. New and better techniques for the recovery of agricultural waste have been developed, based on industrial innovation and high technology, which has contributed to guaranteeing resource efficiency, sustainable production and consumption and the reduction of negative environmental impact.